THE EFFECT OF PREDNISONE ON SERTOLI CELL OF CONTRALATERAL TESTICULAR TORSION - Tanuwidjaja, Dandy; Sugandi, Suwandi; Sihombing, Aaron Tigor Tigor; Yantisetiasti, Anglita; Hernowo, Betthy S. (Indonesian Journal of Urology, 2012)
Objective: To evaluate the effect of prednisone in unilateral testicular torsion on Sertoli cell quality of contralateral testis. Material & Method: Thirty Wistar rats were divided into three groups i.e. group A (sham procedure), group B (unilateral torsion + orchiectomy after 6 hours), and group C (unilateral torsion + orchiectomy after 24 hours). Group B and C were further divided into subgroup with and without Prednisone administration. Prednisone was given orally once a day an hour after torsion, continued till one month later. Orchiectomy of contralateral testis was performed one month later. Those testes were examined by a pathologist. Results: In group A, no abnormality on Sertoli cell quality was found. There is significant difference among groups in Sertoli cell quality (p = 0,01). Ischemic time is associated with Sertoli cell quality (2 rats with severe damage in group C and none in group B). In group B and C, prednisone administration inhibited Sertoli cell damage. Prednisone administration in 6 hours group gave better results than 24 hours group (3 rats vs 1 rat with good Sertoli cell quality). Conclusion: Sertoli cell in contralateral testis is significantly affected by unilateral testicular torsion. Prednisone inhibit Sertoli cells damage. Ischemic time affected Sertoli cell quality of contralateral testis and respond to prednisone.Keywords: Prednisone, unilateral testicular torsion, sertoli cell.